Psychoeducational intervention on burden and emotional well‐being addressed to informal caregivers of people with dementia. Issue 6 (4th October 2020) - Frias, Cindy E.; Risco, Ester; Zabalegui, Adelaida
Abstract: Background: In dementia it is necessary that a family member become an informal caregiver. This labour has social, physical and emotional repercussions on the caregiver's health. The objective was to assesses the impact of the INFOSA‐DEM intervention on burden and emotional well‐being among caregivers of people with dementia, evaluating the effects at 3 and 6 months. Method: We adopted an experimental, non‐randomised design with an intervention group and a control group. The intervention group received the intervention and the control group received usual care. The study was carried out in the catchment areas of three centres specialising in the care of people with cognitive impairment in the province of Barcelona. Results: At 3 months, there was an improvement with respect to burden in the intervention group with a significant worsening ( P < 0.012) in the control group. Similarly, a positive effect on emotional well‐being was observed in the intervention group compared with a small negative effect among controls. Conclusions: Programs addressed to informal caregivers based on psychoeducational and cognitive‐behavioural therapies are effective in improving quality of life and emotional well‐being, and in reducing burden, with a positive effect on the quality of care provided at home.